(untitled) (Caderno Espaço Feminino, 2018)
Resumo O presente artigo objetiva problematizar algumas concepções acerca do que vem a significarÂ Â ser uma mulher negra na sociedade brasileira, bem como suas implicações. Da percepção das práticas racistas, a fazer parte de uma sociedade sexista e patriarcal onde a mulher negra é vítima de opressões que operam interseccionalmente. Palavras-chave:Â Mulher Negra. Estereótipos.Â Racismo. Feminismo. Visibilidade. The Brazilian black woman and the subterfuge of miscegenation to mask colonial rape: the myth of racial democracy and the reinforcement of racist and sexist stereotypes Abstract The present article aims to problematize some conceptions about what it means to be a black woman in Brazilian society, as well as its implications. From the perception of racist practices, to being part of a sexist and patriarchal society where the black woman is the victim of oppressions that operate interseccionalmente. Keywords:Â Black Woman. Stereotypes. Racism.Â Feminism. Visibility.